Comparison of Blood Glucose Values Using Two Glucose Meters and Standard Laboratory Method in Hospitalized Patients in a Teaching Hospital - Shima Aghakachoei; AmirH Zargarzadeh; Masoud Amini (Research Center for Rational Use of Drugs (RCRUD), 2015)
Background: Diabetes mellitus is a chronic disease with a worldwide prevalence and its complications can be prevented with close monitoring of blood glucose. Quality of blood glucose monitoring utilizing glucometers in Iranian hospitalized patients has not been well published in the literature. We evaluated the accuracy and consistency of the results of two devices compared with the standard laboratory method used for measuring glucose levels in a teaching hospital. Methods: In this study 100 patients with the average age of 57.5 ±17.7 years were randomly selected from 19 wards and their blood glucose were simultaneously measured using Accu-Chek Active®(1) and Cleverchek®(2) (commonly used in the wards) and the conventional laboratory method. Calibration was performed on both devices. Results: Absolute Mean Difference of the devices 1 and 2 from the laboratory values were 24.3±2.4,and 38.5±4.5, respectively (P: 0.003). Correlation coefficient of the obtained values by glucometers1 and 2 with lab, were 0.82 and 0.52, respectively. Calibration of the devices showed that device 1 was the most consistent device with the laboratory values, and Pearson correlation coefficient between the obtained values as a result of four reiterations for each sample in each device showed that the highest coefficient belonged to the device 1 and the least belonged to the device 2 used in the Ear, Nose, and Throat Departments. Conclusion: The device 2 used in different wards of the hospital must be calibrated periodically. Furthermore, the device 1 generated closest results to the ones obtained through the laboratory.